2019
DOI: 10.3390/molecules24224025
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Diosgenin-Amino Acid Derivatives with Dual Functions of Neuroprotection and Angiogenesis

Abstract: Diosgenin, a natural product with steroidal structure, has a wide range of clinical applications in China. It also shows great potential in the treatment of blood clots and nerve damage. To enhance the bioavailability as well as efficacy of diosgenin, eighteen diosgenin-amino acid derivatives were designed and synthesized. The neuroprotective effects of these compounds were evaluated by SH-SY5Y cell line and the biosafety was evaluated by H9c2 cell line. The results displayed that part of the derivatives’ acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…After washing with PBS, a Giemsa (Sigma) stock solution was diluted 1 : 10 in PBS and added to the fixed cells for 20 minutes in the dark. 29 Finally, cells were washed with water, dried, and imaged on a Leica DMI4000 B inverted microscope in bright field. In each field of view, the number of dark rounded cells per unit area (μm 2 ) was quantified.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…After washing with PBS, a Giemsa (Sigma) stock solution was diluted 1 : 10 in PBS and added to the fixed cells for 20 minutes in the dark. 29 Finally, cells were washed with water, dried, and imaged on a Leica DMI4000 B inverted microscope in bright field. In each field of view, the number of dark rounded cells per unit area (μm 2 ) was quantified.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, the compound diosgenyl salicylate conjugates, obtained by the pyridine-catalyzed esterification of diosgenin with 2-acetoxybenzoyl chloride, showed the highest anti-inflammatory activity. (Cai et al, 2019) improved the solubility and physicochemical properties of diosgenin by introducing different amino acids at the C-3 position of diosgenin, due to the neuroprotective effect of amino acids, and a series of amino acid derivatives of diosgenin were synthesized, which were tested to show that most of the derivatives were better than the raw material, with 3β-(L-isoleucine)-diosgenin having neuro dual role of neuroprotection and angiogenesis. The synthetic pathway is shown in Figure 3.…”
Section: Diosgenin Derivativesmentioning
confidence: 99%
“…Another study by (Wang et al, 2015b) summarized the current conformational relationships between diosgenin and its derivatives, obtaining the corresponding activities of different derivatives of this substance, different derivatives as intermediates of active ingredients of different drugs or final forms of activity presentation. In addition, it was shown that the amino acid derivatives of diosgenin have neurosynthetic and angiogenic effects, and their corresponding series of derivatives target enhanced neuroprotection compared to diosgenin, especially the compound DG-15, which has stronger activity and lower cytotoxicity than diosgenin, and is an important direction for the future development of drugs such as vascular activators (Cai et al, 2019). It has been studied that diosgenin-betulinic acid conjugates have the ability to enhance and/or alter the pharmacological properties of the substance's own components (Özdemir et al, 2020).…”
Section: Effects On Tracheal Smooth Musclementioning
confidence: 99%
“…The neuroprotection of natural products has been discovered to modulate activities via multiple targets and signaling pathways with direct or indirect effects on enzymes, such as kinases, receptors and proteins ( Bagli et al, 2016 ). This wide band of pharmacological or biological activities has made them suitable candidates for the treatment of stroke ( Cai et al, 2019 ; Zhang, C. et al, 2020 ; Zhong et al, 2020 ). As a requirement of novel drug development for stroke, there is a focus on the neuroprotection of natural products via multi-targets.…”
Section: Introductionmentioning
confidence: 99%